Innovative Technologies Application in Education as a Condition for Education for Society Sustainable Development - Rybalko, Lina; Lavrentieva, Elena; Voloshko, Larisa; Rozhenko, Inessa (International Journal of Engineering and Technology, 2018)
The article presents the results of the scientific research on the issue of environmental studies based on ecological-evolutionary approach. The meaning and content of the term ecological-evolutionary approach and the conceptual ideas of ecological-evolutionary approach (the idea of evolution and ecocentrism) are explained. Teaching technologies based on ecological-evolutionary approach are characterized with the approach explained as the innovative technology that, in use, will provide modernization of environmental studies within the educational aspect for the societyâ€™s sustainable development. The pedagogical experiment results are presented, confirming the technologyâ€™s effectiveness based on ecological-evolutionary approach and the implementation of ecological-evolutionary approach concepts and didactic fundament in teaching environmental subjects. Â Â